2022
DOI: 10.3390/mi13071038
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Crosslinkable Hydrogels for 3D Bioprinting in the Repair of Osteochondral Defects: A Review of Present Applications and Future Perspectives

Abstract: An osteochondral defect is a common and frequent disease in orthopedics and treatment effects are not good, which can be harmful to patients. Hydrogels have been applied in the repair of cartilage defects. Many studies have reported that hydrogels can effectively repair osteochondral defects through loaded cells or non-loaded cells. As a new type of hydrogel, photo-crosslinked hydrogel has been widely applied in more and more fields. Meanwhile, 3D bioprinting serves as an attractive platform to fabricate custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 152 publications
0
11
0
Order By: Relevance
“…The most significant advantage of digital light printers is the ability to print small scaffold designs at resolutions on the order of 10 µm. A disadvantage to photo-crosslinking is that UV light can damage cell DNA, leading to reduced cell viability [ 8 , 13 , 15 ]. Each bioprinting technique has advantages and disadvantages.…”
Section: Bioprinting Technologies; Advantages and Disadvantagesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most significant advantage of digital light printers is the ability to print small scaffold designs at resolutions on the order of 10 µm. A disadvantage to photo-crosslinking is that UV light can damage cell DNA, leading to reduced cell viability [ 8 , 13 , 15 ]. Each bioprinting technique has advantages and disadvantages.…”
Section: Bioprinting Technologies; Advantages and Disadvantagesmentioning
confidence: 99%
“…PEGDA hydrogels possess biocompatibility and the capability to be loaded with specific cells and biological factors. UV cross-linking has been shown to improve mechanical properties [ 5 , 8 , 54 ]. Silk fibroin (SF) is a protein polymer that is biocompatible, cytocompatible, possesses mechanical strength, and is biodegradable.…”
Section: Decm and Bioinks For Cartilage Regeneration And Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, hydrogel composition and structure should mimic the native cartilage tissue, being able to withstand mechanical stress, especially in load-bearing joints. Among several approaches adopted to tune the mechanical properties, partial oxidation of PVA has been proposed through a chemical reaction with different oxidizing agents, namely potassium permanganate (KMnO 4 ), bromine (Br 2 ), and iodine (I 2 ) [ 27 , 28 , 29 ]. Partially oxidized PVA hydrogels demonstrated high biocompatibility, good protein delivery capacity, and improved biodegradability in both in vitro and in vivo studies testing the polymer material not only for cartilage substitution [ 27 ], but also for peripheral nerve [ 30 ] and gut [ 31 ] TE.…”
Section: Introductionmentioning
confidence: 99%
“…Among several approaches adopted to tune the mechanical properties, partial oxidation of PVA has been proposed through a chemical reaction with different oxidizing agents, namely potassium permanganate (KMnO 4 ), bromine (Br 2 ), and iodine (I 2 ) [ 27 , 28 , 29 ]. Partially oxidized PVA hydrogels demonstrated high biocompatibility, good protein delivery capacity, and improved biodegradability in both in vitro and in vivo studies testing the polymer material not only for cartilage substitution [ 27 ], but also for peripheral nerve [ 30 ] and gut [ 31 ] TE. Regarding the mechanical behavior, uniaxial tensile tests showed that the oxidation treatment reduces PVA stiffness to a different extent depending on the oxidizing agent.…”
Section: Introductionmentioning
confidence: 99%